The relationship between knowledge, attitude, and family support with mother’s behaviour in treating of acute respiratory infection on children under five at Desa Bangunjiwo, Kasihan Bantul - Octaviani, Dini; Kholisa, Itsna Luthfi; Lusmilasari, Lely (International Journal of Research in Medical Sciences, 2017)
Background: Acute respiratory infection (ARI) is a disease that often affects infants and children (Depkes RI, 2008). The prevalence of ARI in Indonesia was 25.0 percent (Riskesdas, 2013. Mothers have an important role in controlling ARI in infants. However, there are many women who are poorly behaving when dealing with children who suffer from respiratory. Mother's behavior is influenced by the knowledge, attitude and family support. The purpose of this study was aimed at determine the relationship between knowledge, attitudes and family support with mothers ‘behavior in handling of ARI in children under five years old. Methods: This is a correlative study, using a quantitative method with cross sectional design. Bivariate analysis was used to determine the relationship between knowledge, attitudes and support for families with mothers ‘behavior using the Spearman test. The four variables are numeric variable with α ˂ 0.05 and 95 % CI. Linear regression analysis was used to determine the independent variable that most strongly linked with the dependent variable. Results: The results showed an association between attitudes and behavior with p=0.001 and r=0.393. Family support is also related to the behavior with p=0.001 and r=0.400. Knowledge does not have a relationship with the mother's behavior. The results of linear regression analysis, family support is the variable that mostly linked to behavior (p=0,003). Conclusions: There is a relationship between attitudes and family support with mothers ‘behavior. Family support is the variable that most strongly linked to the mothers ’behavior.